Central Sulawesi Provincial Government Management in Conducting Political Development to Support Conducive Regional Development - Eman Sulaeman Nasim (Riwayat: Educational Journal of History and Humanities, 2024)
Political stability in Central Sulawesi plays an important role in implementing conducive regional development. The relationship between political stability and development is very close where political stability creates an environment that is conducive to development. The level of political stability of a region directly influences its level of development. When an area experiences political instability, development will definitely be disrupted. Investors tend to be reluctant to invest because of the uncertain risks. Political stability allows the government to design and implement long-term policies that encourage sustainable economic growth and societal welfare. The role of Political Institutions in maintaining the stability of political institutions, such as parliament, courts and other government bodies, has a major responsibility in maintaining political stability through supervision, balance of power, and fair and transparent application of laws. Good regional government management will be able to unite various political interests and act fairly to help create a conducive political climate to support regional development. The role of Regional Government Management (Executive, Legislative, Judiciary), Political Parties (Parpol), social organizations (Ormas), Non-Governmental Organizations (NGOs), press institutions, journalist organizations and the active participation of the community in the political process also have a big influence on political stability.